THE ROLE OF THE COACH FOR THE PERSONAL AND ACADEMIC DEVELOPMENT OF YOUNG ATHLETES: QUALITATIVE RESEARCH - Sedyankova, Rayna (E-Journal VFU, 2025)
This article presents findings from a qualitative study based on semi-structured interviews with coaches in the field of sports dance. The aim of the study is to explore the perceptions of coaches regarding their role as a key factor in the personal and academic development of adolescent athletes of school age. Through thematic analysis of the collected interview data, recurring themes, patterns, and trends are identified, highlighting the influence of the coach not only on athletic performance but also on academic motivation, learning strategies, self-reflection, and discipline among young dancers. The results emphasize the multifaceted role of the coach as both an athletic guide and a contributor to the holistic development of youth, particularly in the context of balancing sporting commitment and educational engagement.
Keywords: academic motivation; personal development; coach; adolescents; sports dance; qualitative research; motivational patterns